WSDL automatic generation from UML models in a MDA framework - Vara, J; de Castro, V; Marcos, E (2005)
In this work, we introduce the MIDAS-CASE subsystem for Web Services. MIDAS-CASE is a MDA tool for Web Information Systems development. Using an extension of UML language for representing the Web Services Description Language standard, the MIDAS-CASE subsystem proposed supports the modeling of Web Services in extended UML and the automatic generation of the respective WSDL description for the Web Service modeled.